Tinjauan Cakupan: Faktor-faktor yang Berkontribusi pada Keberhasilan Intervensi Berbasis Komunitas dalam Meningkatkan Asupan Protein Hewani pada Anak Usia 6–23 Bulan (Studi di Negara Berpendapatan Rendah dan Menengah) - Fathimah Asri Fadhilah Aulia; Sri Achadi Nugraheni; Siti Fatimah Pradigdo; Muflihatun Nisa (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Purpose: The intake of animal protein among children aged 6–23 months in low-income and middle-income countries remains far below WHO recommendations. This scoping review aims to map community health worker–based interventions in improving animal protein intake during complementary feeding. Methods: Through a systematic search of the Scopus, PubMed, and EBSCOhost databases, 12 studies from various low-income and middle-income countries were analyzed using the Joanna Briggs Institute appraisal tool. Twelve studies from Africa, Asia, and Latin America met the inclusion criteria. All studies reported improvements in maternal knowledge related to animal-source protein (ranging from 19% to 37%) and positive changes in complementary feeding practices, including increased consumption of animal-source foods and improved dietary diversity. Several studies also demonstrated favorable impacts on child nutritional status, with reductions in stunting of up to 8.1%. Five main intervention strategies were identified: face-to-face nutrition education, community-based behavior change communication, home visits, combined lipid-based supplementation, and practical learning approaches. Ten enabling factors were consistently reported, particularly adequate CHW training, strong health system support, high CHW motivation, family involvement, and availability of local animal-source foods. Conversely, nine major barriers were identified, most notably household economic constraints, which were reported across all studies. Conclusion: Community-based interventions led by community health workers are effective in improving animal-source protein intake and complementary feeding practices among children under two years of age in LMICs. Program success depends on the interaction between well-trained and supported CHWs, enabling household and community environments, and broader socioeconomic conditions. Addressing structural barriers, especially household economic limitations, is essential to sustain and scale up effective interventions.